ANALYSIS OF ANXIETY LEVEL OF PREMENOPAUSE IN KARAJAN BARAT VILLAGE OF CIKAMPEK BARAT DISTRICT OF KARAWANG REGENCY IN 2021 - irmayanti Irmayanti; Anni Suciawati; Rukmaini (Politeknik Medica Farma Husada Mataram, 2021)
Development and growth in the human body process along with increasing age. The development and growth in the process will change gradually according to the stages. Most of these changes occur in women because in the aging process a phase occurs, namely the menopause phase. Many premenopausal women complain that with the arrival of menopause they will become anxious, they are anxious towards the end of their reproductive period and realize that they will grow old which means their beauty will fade and the function of their organs will decrease, thereby eliminating their pride as a woman This study aims to determine the factors associated with premenopausal anxiety levels in Karajan Barat Village of Cikampek Barat District of Karawang Regency in 2021. This study uses a correlational analytic study with a cross-sectional approach. The sample in this study amounted to 72 premenopausal women. The sampling technique used the purposive sampling technique. The research instrument consisted of a questionnaire about education level, knowledge level, financial material assets, family support, and socio-cultural support. This questionnaire has been tested for validity using Cronbach's alpha with an r table value of 0.514 and reliability testing with a value >0.6. The anxiety questionnaire using Hamilton Rating Scale for Anxiety (HAR-S). The data were analyzed using the chi-square correlation test with a significant level of <0.05 to determine the relationship between education level, knowledge level, financial material assets, family support, and socio-cultural support with premenopausal anxiety level. The results showed that the relationship between education level and anxiety obtained a p-value of 0.689 (p>0.05). The relationship between the level of knowledge and anxiety obtained a p-value of 0.009 (p <0.05). The relationship between financial material assets and anxiety has a p-value of 0.58 (p>0.05). The relationship between family support and anxiety has a p-value of 0.001 (p <0.05). The socio-cultural relationship between support and anxiety has a p-value of 0.000 (p<0.05). The conclusion of this research is there is a significant relationship between the level of knowledge, family support, and socio-cultural support to the level of anxiety of premenopausal. There is no significant relationship between the level of education and financial material assets on the level of anxiety of premenopausal women. Keywords: Premenopausal, Education, Knowledge, Financial Material Assets, Family Support, Socio-Cultural Support, Anxiety.